2017
DOI: 10.1021/acssuschemeng.6b02867
|View full text |Cite
|
Sign up to set email alerts
|

Thin Cellulose Nanofiber from Corncob Cellulose and Its Performance in Transparent Nanopaper

Abstract: Cellulose separated from corncob was used as a new cellulose resource to produce esterified cellulose nanofiber (E-CNF) with hexanoyl chloride through one-step mechanochemical esterification by ball milling. The result showed that corncob cellulose was easily disintegrated and esterified to achevie a high DS, and then, thin nanofiber was compared to the common pulp cellulose resource. The DS of E-CNF was as high as 0.95, and the diameter was about 1.5–2.8 nm. Then, E-CNF was formed to nanopaper by vacuum filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Herrick et al (1983) presented a method for the isolation of acetylated NFC using a mixture of acetic acid and acetic anhydride with sulfuric acid as catalyst. Huang and coworkers reported a similar onestep procedure via mechanochemical strategy in an organic solvent aiming to esterify and defibrillate cellulose fibers simultaneously , Huang et al 2016Kang et al 2017;Rao et al 2015). The method consists of ball milling solid cellulose in a non-aqueous solvent loaded with an esterifying agent.…”
Section: In Situ Esterification During the Isolation Of Nanocellulosesmentioning
confidence: 99%
“…Herrick et al (1983) presented a method for the isolation of acetylated NFC using a mixture of acetic acid and acetic anhydride with sulfuric acid as catalyst. Huang and coworkers reported a similar onestep procedure via mechanochemical strategy in an organic solvent aiming to esterify and defibrillate cellulose fibers simultaneously , Huang et al 2016Kang et al 2017;Rao et al 2015). The method consists of ball milling solid cellulose in a non-aqueous solvent loaded with an esterifying agent.…”
Section: In Situ Esterification During the Isolation Of Nanocellulosesmentioning
confidence: 99%
“…The specimens were prepared by grinding the sample with KBr (1:100, w/w) and then pressing into an ultrathin disc. Degree of substitution (DS) of E-MCC was calculated by weight gain according to the following equation [25]:…”
Section: Ultrasound Treatment: a 22 Khz Ultrasound Generator (Hn-1000mentioning
confidence: 99%
“…These vary upon their sizes and functionality (Abitbol et al, 2016). Amiralian et al, 2015;Kang et al, 2017;Wijaya et al, 2019 Cellulose Nano-Fibrils (CNFs)…”
Section: Nano-cellulose Types and Propertiesmentioning
confidence: 99%
“…Habibi and coworkers in 2010 found that nanoparticles were extracted from the cotton, which has a dimension of 70-300 nm in length and 5-11 nm in width (Habibi et al, 2010). Similarly, Kang et al reported that corncob wastage of ball milling was used as sources for CNF production through a step mechanochemical esterification process (Kang et al, 2017). Additionally, Pandey and colleagues in 2015 revealed that the production of CNF through newspaper waste has a significant impact on the ecosystem and is economically important (Pandey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%